If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(x + 2) + -1(2x + -7) = 0 Reorder the terms: 6(2 + x) + -1(2x + -7) = 0 (2 * 6 + x * 6) + -1(2x + -7) = 0 (12 + 6x) + -1(2x + -7) = 0 Reorder the terms: 12 + 6x + -1(-7 + 2x) = 0 12 + 6x + (-7 * -1 + 2x * -1) = 0 12 + 6x + (7 + -2x) = 0 Reorder the terms: 12 + 7 + 6x + -2x = 0 Combine like terms: 12 + 7 = 19 19 + 6x + -2x = 0 Combine like terms: 6x + -2x = 4x 19 + 4x = 0 Solving 19 + 4x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-19' to each side of the equation. 19 + -19 + 4x = 0 + -19 Combine like terms: 19 + -19 = 0 0 + 4x = 0 + -19 4x = 0 + -19 Combine like terms: 0 + -19 = -19 4x = -19 Divide each side by '4'. x = -4.75 Simplifying x = -4.75
| 6y+4-2y=1+3y-7 | | x(28-x)=192 | | (8x+5)-(6x-7)= | | -4(4b+4)+(17b-3)=0 | | -90z-0.9=-100z+1.5 | | 90z-0.9=-100z+1.5 | | -7(5y+7)= | | 2.1q-5.2-3.5q=-2.4q-4.1 | | x^3-5x^2-11x-3=0 | | 4m+8=-8 | | 190=L+9(w) | | 5t-t-8=3t-6 | | 8z+z=8z+5 | | 42=2(l)(w) | | 2(2x+40)2x=680 | | 2(x+40)+x=680 | | 6+2(3m-4)-16m= | | 2(x+40)+2x=680 | | 5t-t-8=3t+6 | | -16+4=-2(x+3) | | -16+4=-2(2x+3) | | 1-3(y-5)=-5(y-2) | | 5(x-4)+6=2x+3(-4+x) | | 6.1x-3+x-1.9= | | r-8.5=-8.1 | | -2(7x-7)+1=-14x+15 | | (7y+6)-(2+6y)=9 | | (x-1)(x-4)(x-6)+(-2)(-5)(-3)+(-3)(-2)(-5)-(-2)(-2)(x-6)-(x-1)(-5)(-5)-(-3)(x-4)(-3)=0 | | pe=9c | | 4y+4y=7y-5 | | [5-2(5-4)]= | | (w+23)+(4w+7)=18 |